Maqashid al-Syari'ah: Philosophical Review of the concept of Thair ibn 'Asyur - Mashar, Aly (SHAHIH: Journal of Islamicate Multidisciplinary, 2022)
This manuscript attempts to elaborate on the concept of maqashid al-syari'ah as a separate science based on Ibn 'Asyur perspective. It examines the concept using a philosophy of science perspective whether Ibn 'Asyur's idea has met the scientific criteria. It also uses library research within a content analysis theory. The main source of this manuscript derived from the book Maqashid al-Syari'ah al-Islamiyah by Ibn 'Asyur published by Dar al-Nafais. The result shows that the concept of maqashid al-syari'ah Ibn 'Asyur contains scientific criteria based on assumption, ontology, epistemology, and axiology.